Analysis of Erosion Mitigation on Bridge Pillars - Hidayat, Acep; Suprapti, Suprapti; Isradi, Muhammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Scour on bridge piers is a major problem in hydraulic engineering, reducing structural stability and accelerating foundation failure. This phenomenon occurs due to the interaction between airflow and bridge structural elements, resulting in the formation of scour holes that potentially reduce the bearing capacity of the soil around the piers. In areas with strong currents, seasonal changes in discharge, and unstable riverbed conditions, the risk of scour is even higher. The impact of scour damage not only reduces the operational lifespan of bridges but also leads to high rehabilitation costs and increases the potential for structural failure, which can endanger user safety. This study aims to analyze various scour mitigation methods that can be applied to bridge piers, including the use of protective materials such as riprap, gabions, and geotextiles; a geotechnical engineering approach that includes soil stabilization and riverbed contour modification; and the development of pier structural designs that are more adaptive to variations in flow patterns. The study was conducted through an in-depth literature review of previous research, an analysis of the effectiveness of each method under various hydrodynamic conditions, and an evaluation of the cost. The results of this study are expected to produce comprehensive recommendations regarding the most effective, efficient, and environmentally friendly mitigation strategies to reduce the rate of scour. Furthermore, this study provides direction in planning bridge designs that are more resilient to changes in flow and sedimentation, thereby extending the service life of the structure, reducing long-term maintenance costs, and improving user safety.